Analisis Pengguna Media Sosial Terhadap Isu UU Cipta Kerja Menggunakan SNA dan Naive Bayes - Mau, Stevanus Dwi Istiavan; Sembiring, Irwan; Purnomo, Hindriyanto (Building of Informatics, Technology and Science (BITS), 2022)
In research about analysis issue analysis, UU Cipta Kerja aims to investigate aktor which has the most influence in the discussion on the network is based on the analysis of the most popular centrality values on the issues law copyright this working. Research is in use of the method of Social Network Analysis ( SNA ). The data in minutely as many as 1686 nodes and 1403 edges in extract through the API Twitter with the help of application WinPython and Netlytic with a period 08 October 2020 - 05 July 2021. The result of this research showed that account @BEMUI_ Official is account the most popular with the Degree Centrality 944, value Betweenness Centrality 640042.0. But on a calculation Closeness Centrality aktor @BEMUI_Official having value 0.701235, therefore nodes who have a centrality highest do not necessarily have the value that both in terms of the dissemination of information.